The Department of Defense posture for artificial intelligence assessment and recommendations - Tarraf, Danielle C.; Shelton, William L. 1954-; Parker, Edward; Alkire, Brien; Carew, Diana; Grana, Justin; Levedahl, Alexis; Leveille, Jasmin; Mondschein, Jared; Ryseff, James; Wyne, Ali (RAND Corporation, 2019)
The 2019 National Defense Authorization Act mandated a study on artificial intelligence (AI) topics. In this report, RAND Corporation researchers assess the state of AI relevant to the U.S. Department of Defense (DoD), and address misconceptions about AI; they carry out an independent and introspective assessment of the Department of Defense's posture for AI; and they share a set of recommendations for internal actions, external engagements, and potential legislative or regulatory actions to enhance the Department of Defense's posture in AI.
"December 2019."
"RAND National Defense Research Institute."
"Prepared for the Office of the Secretary of Defense."
"This research was ... conducted within the Acquisition and Technology Policy Center of the RAND National Defense Research Institute"--Preface (page iv)
Keywords: United States / Department of Defense; Artificial intelligence / Military applications / United States; Artificial intelligence / Military applications; United States